Debt Valuation, Renegotiation, and Optimal Dividend Policy - Fan, Hua; Sundaresan, Suresh M. (Review of Financial Studies, 2000)
The valuation of debt and equity, reorganization boundaries, and firm's optimal dividend policies are studied in a framework where we model strategic interactions between debt holders and equity holders in a game-theoretic setting which can accommodate varying bargaining powers to the two claimants. Two formulations of reorganization are presented: debt-equity swaps and strategic debt service resulting from negotiated debt service reductions. We study the effects of bond covenants on payout policies and distinguish liquidity-induced defaults from strategic defaults. We derive optimal equity issuance and payout policies. The debt capacity of the firm and the optimal capital structure are characterized.